Perubahan Hati Terkait Pertumbuhan Oosit Ikan Sebelah (Psettodes erumei) (Changes in Liver relate to Oocyte Growth of Flatfish) - Tresnati, Joeharnani; Umar, Moh. Tauhid; Sulfirayana, Sulfirayana (Program Studi Manajemen Sumber Daya Perairan, 2018)
There are 8 species of flatfish in the waters of the Spermonde archipelago, South Sulawesi, but only one has thick body, that is Psettodes erumei. Development of flatfish P.erumei populations can be done if its reproductive aspect is known. In this study we will examine the changes of liver through the Hepatosomatic Index (HSI) associated with the growth of oocytes based on Gonad Maturity Stage (GMS). The Hepatosomatic Index (HSI) is defined as the ratio of weight body to weight liver. The value of this index gives an indication of the status of energy reserves in animals. The results of this study indicate a change in liver weight based on HSI which increases following the increase of oocyte size based on GMS. HSI increased sharply after GMS II and ahead of GMS III, which then increase not too big again after GMS III. This suggests an increase in food reserves stored in the liver, to support the oocyte reaching the beginning of its gonad maturity.Keywords : Hepatosomatic Index (HSI), Gonad Maturity Stage (GMS), Oocyte, Reproduction, Flatfish Psettodes erumei